Altered Mental Status in the Emergency Department - Smith, Austin T.; Han, Jin H. (Seminars in Neurology, 2019)
Altered mental status is an umbrella term that covers a broad spectrum of disease processes that vary greatly in chronicity and severity. Causes can be a primary neurologic insult or a result of a systemic illness resulting in end-organ dysfunction of the brain. Acute changes in mental status are more likely than chronic changes to be immediately life-threatening and are therefore the focus of this review. Given the potential time-sensitive nature, acute changes in mental status must be addressed immediately and with urgency. We recommend a primary survey followed by a secondary survey with special attention to immediate life-threatening reversible causes. We then recommend a systems-based approach searching for any other life-threatening or reversible causes. Because the differential for altered mental status is broad, a comprehensive emergency department evaluation including a detailed history and physical exam as well as laboratory and radiographic testing is needed.
Keywords: altered mental status; confusion; altered behavior; generalized weakness; lethargy; agitation; psychosis; disorientation; inappropriate behavior; hallucination